Prototyping of Self-Sufficient Marine Propulsion Systems (JOURNAL OF ADVANCES IN PHYSICS, 2026)
This work presents the development of a marine propulsion system with a net-zero emissions energy supply. While the final propulsion element remains a conventional propeller or water-jet, the primary innovation lies in its power source. The main challenge is to create an energy supply that is not only carbon-neutral, but also self-sufficient, viable, and reliable. To achieve this, we propose a disruptive shift: replacing conventional fossil-fuel engines with a Self-Sufficient Power Machine (SSPM). This disruptive approach eliminates the need for traditional fuel storage and allows autonomous vessels to integrate SSPM-based resources for powering all services, including critical systems. Since it requires no fossil fuel or any other type of fuel, it offers unlimited autonomy. This advantage is essential for submarines and other submersible vehicles.The results, based on a generic case study with seven cascaded power units operating at temperatures between 300 and 1000 K, confirmed the following regarding self-sufficiency: The calculated net positive output of 1513 kJ/kg-cycle after considering feedback heat demonstrates the system's ability to maintain its own operation while generating a significant amount of free work.